Agente Integrador de Recursos Energéticos Distribuidos como Oferente de Energía en el Nivel de Distribución - Arias Barragán, Luis Alejandro; Rivas Trujillo, Edwin; Santamaria, Francisco (Ingeniería, 2017)
Context: It has been observed the incipient development of the integration of Distributed Energy Resources (DER) in electricity markets at the distribution level. Method: DER participation by an integrator agent is proposed. The integrator agent allows DER to participate as suppliers of energy to the network operator and / or the energy market at the distri-bution level. Sequence diagrams and mathematical formulas were proposed, for fixing the price of energy by relying on a case study. Results: The results show the feasibility of the integrator agent to participate as a supplier of elec-tricity to the distribution network. Conclusions: Applications using cloud computing allow users to access information on the DER agent resources in general and to the state of the network demands. Pricing schemes proposed al-low DER participation through the integrating agent as a supplier of energy.